Veto Players and Policy Trade-Offs- An Intertemporal Approach to Study the Effects of Political Institutions on Policy - Carlos Scartascini; Mariano Tommasi; Ernesto Stein (Inter-American Development Bank (IDB), 2010)
The capacity to sustain policies over time and the capacity to adjust policies in the face of changing circumstances are two desirable properties of policymaking systems. The veto player approach has suggested that polities with more veto players will have the capacity to sustain policies at the expense of the ability to change policy when necessary. This paper disputes that assertion from an intertemporal perspective, drawing from transaction cost economics and repeated game theory and showing that some countries might have both more credibility and more adaptability than others. More generally, the paper argues that, when studying the effects of political institutions on policy outcomes, a perspective of intertemporal politics might lead to predictions different from those emanating from more a-temporal approaches.
Keywords: D72; D78; H10; H50; 330; Political institutions; Public policies; Veto players; Policy adaptability; Policy stability; Intertemporal; Credibility; Repeated games